Answer:
Step-by-step explanation:
(m^3/4c5)(-4)
Final result :
m(-12)c(-20) • 28
—————————————————
1
Reformatting the input :
Changes made to your input should not affect the solution:
(1): "^-4" was replaced by "^(-4)".
Step by step solution :
Step 1 :
m3
Simplify ——
4
Equation at the end of step 1 :
m3
(—— • (c5))-4
4
Step 2 :
Equation at the end of step 2 :
(m3c5)
(——————)-4
4
Step 3 :
3.1 m3 raised to the minus 4 th power = m( 3 * -4 ) = m-12
3.2 c5 raised to the minus 4 th power = c( 5 * -4 ) = c-20
3.3 4 = 22 (4)-4 = (22)(-4) = (2)(-8)
Final result :
m(-12)c(-20) • 28
—————————————————
1